2016
DOI: 10.3389/fphar.2016.00432
|View full text |Cite
|
Sign up to set email alerts
|

Feto-Maternal Trafficking of Exosomes in Murine Pregnancy Models

Abstract: Timing and initiation of labor are well-orchestrated by signals communicated between the fetal and maternal compartments; however, how these signals are communicated is not completely understood. Fetal exosomes, intercellular signaling vesicles, may play a key role in the process. The objective of this study was to evaluate exosome trafficking in vivo from fetal to maternal compartments. Pregnant CD-1 mice were intra-amniotically injected on gestational day 16 and 17 with exosomes isolated from primary human a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 47 publications
2
75
0
Order By: Relevance
“…These exosomes can either diffuse through tissue layers or reach their destination via the systemic route. Animal model experiments have confirmed trafficking of fetal exosomes through both mechanisms in which intraamniotic injection of exosomes resulted in their localization in both maternal blood as well as uterine tissues (Sheller-Miller et al, 2016). Thus, senescent fetal cells can package inflammatory mediators inside exosomes and transport them to other uterine destinations.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…These exosomes can either diffuse through tissue layers or reach their destination via the systemic route. Animal model experiments have confirmed trafficking of fetal exosomes through both mechanisms in which intraamniotic injection of exosomes resulted in their localization in both maternal blood as well as uterine tissues (Sheller-Miller et al, 2016). Thus, senescent fetal cells can package inflammatory mediators inside exosomes and transport them to other uterine destinations.…”
Section: Discussionmentioning
confidence: 91%
“…Media were thawed at 4°C overnight prior to isolation. Exosomes were isolated as described (Sheller-Miller et al, 2016; Sheller et al, 2016) with the following modifications. After centrifugation at 2000 g, the supernatant was transferred to Amicon Ultra 15 centrifugation filters (Millipore, Billerica, MA) and centrifuged at 2000 g for 90 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, animal model studies have shown that exosomes injected into the amniotic fluid cavity access the maternal tissues by local and systemic routes. 40 There are several studies which have reported exosome trafficking between tissues 41, 42 and that indicate exosomes are released from cells from both the apical and basolateral compartments. 4347 Although these data support the core hypothesis that exosomes from the fetus access maternal tissues, the capacity for fetal exosomes in induce inflammatory changes in the maternal tissues remains unknown.…”
Section: Introductionmentioning
confidence: 99%